Genomics Approaches to Deciphering Natural Transformation in Cyanobacteria - Wendt, Kristen E.; Pakrasi, Himadri B. (Frontiers in Microbiology, 2019)
Natural transformation is the process by which bacteria actively take up and maintain extracellular DNA. This naturally-occurring process is widely used as a genetic modification method in bacterial species, and is crucial for the efficient genetic modification of organisms in an industrial setting. Cyanobacteria are oxygenic photosynthetic microbes that are promising platforms for bioproduction of fuels, chemicals, and feedstocks. Using CO2 and sunlight alone, cyanobacteria can make these valuable bioproducts in a carbon-neutral manner. While genetic modifications have been performed in a number of cyanobacterial strains, natural transformation has been successfully demonstrated in only a handful of species. Even though thousands of cyanobacterial strains have been deposited in culture collections and hundreds of these species have had their genomes sequenced, only a few of these organisms have been experimentally transformed. Although there are many aspects of cyanobacterial biology that provide exciting opportunities for biological investigation, the absence of a rapid and straightforward genetic modification method such as natural transformation hinders research efforts to understand some of the fascinating nuances of cyanobacterial physiology. The ability to use natural transformation in more strains of cyanobacteria would facilitate the rapid employment of these organisms in bioproduction settings. This article discusses recent advances in the understanding of natural transformation in cyanobacteria. Additionally, it identifies gaps in the current knowledge about cyanobacterial natural transformation and provides an overview of how new genomic technologies may be implemented to understand this important process.